APPLICATION OF A CONTINUOUS WAVELET TRANSFORMS AND ANFIS TO FAULT DIAGNOSIS OF A GEARBOX OF TRACTOR - Bahrami, Mostafa; Javadikia, Hossein; Ebrahimi, Ebrahim (Journal of Mechanical Engineering, 2017)
This study proposes a technique based on continuous wavelet transform added by adaptive-neural-fuzzy inference system (ANFIS) for fault diagnosis of gearbox of MF285 tractor. Varying fault can cause changes in a measured gearbox vibration signal. A gear motion vibration signal in speed of 1500 r/min is analyzed as source data. Energy of coefficients wavelet is proposed to evaluate tractor gear fault by ANFIS. We found that this technique can correctly indicate early gear fault.